2022
DOI: 10.1177/2156759x221086739
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review Exploring Achievement Outcomes and Therapeutic Factors for Group Counseling Interventions in Schools

Abstract: This article presents a systematic review of group counseling interventions facilitated by school counselors that included academic achievement as outcome targets. We examined the articles that met the criteria to identify any therapeutic factors within the group interventions. A total of 18 articles met the criteria and all of the studies with the largest effect size (i.e., above .8) were found to have imparting information as one of the therapeutic factors coded as part of the intervention. Five articles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In both our study and that of Steen et al (2007), the majority of the participants were White but other racial categories were represented. In other research, Steen et al (2021) discovered that both White and non-White school counselors conducted group interventions; however, some school counselors also served student populations that included a majority of non-White participants. Weinstein and colleagues (2021) found that school counselors could use group interventions to produce positive achievement outcomes that were quantitative in nature for Black and brown students in school settings and the school counselor’s racial identity was not a factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both our study and that of Steen et al (2007), the majority of the participants were White but other racial categories were represented. In other research, Steen et al (2021) discovered that both White and non-White school counselors conducted group interventions; however, some school counselors also served student populations that included a majority of non-White participants. Weinstein and colleagues (2021) found that school counselors could use group interventions to produce positive achievement outcomes that were quantitative in nature for Black and brown students in school settings and the school counselor’s racial identity was not a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Steen and colleagues (2022) culled the school counselor literature to find interventions that were created specifically for Black male youth. These researchers discovered that school counselors working with Black male youth infused aspects of Black history, contemporary Black leaders, and current societal events involving the Black community within their interventions as a form of resistance to the racism the students experienced within schools and society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunity for students, especially Black youth, to openly express themselves in a nonthreatening, supportive environment is essential and helps them benefit from effective groups (Harris et al, 2020). More important, a supportive environment helps students of color to feel empowered by their intersections of identity, not limited to their cultural identities such as their race and gender, and this can lead to healthy identity development (Steen, Melfie, et al, 2022;Steen, Vannatta, et al, 2022).…”
Section: Group Counseling Programs and Racial Identity Developmentmentioning
confidence: 99%
“…School counselors work diligently, day in and day out, conducting classroom lessons and counseling students individually (American School Counselor Association [ASCA], 2023). However, small-group counseling remains one of the most effective ways to engage multiple students with similar needs (Steen et al, 2022). Small-group counseling in schools can be complex and challenging.…”
mentioning
confidence: 99%